F(x)+2x^2-4x-3 g(x)=2x^2-16 find f(x)+g(x)

Answers

Answer 1
Answer: f(x) = 2x^2 - 4x - 3
g(x) = 2x^2 - 16

f(x) + g(x)
2x^2 - 4x - 3 + 2x^2 - 16
4x^2 - 4x - 19

Related Questions

Which statement is true about the graph ofthe function y = 3|x – 2| + 4?A Its vertex is at (-6,0)B Its vertex is at (-2, 4)C Its vertex is at (2, 4)D Its vertex is at (4,2)
A line has a y-intercept of -5 and passes through the point (-3, 1). write the equation of the line.
A recent study indicates that the annual cost of maintaining and repairing a car in a town in Ontario averages 200 with a variance of 260. A tax of 20% is introduced on all items associated with the maintenance and repair of cars (i.e., everything is made 20% more expensive). Calculate the variance of the annual cost of maintaining and repairing a car after the tax is introduced.
Help asap pls !!! I am stuck for like 15 mins
Wendy is arranging books on the bookshelves in the school library. The total number of books she arranges is given by the equation b = 12r, where b is the total number of books and r is the number of rows. Each row contains the same number of books.If Wendy arranged 16 rows she arranged a total of what books

What is the 16th term in the sequence?

2, 6, 18, 54, 162, . . .

Answers

it was a hard one but the answer is 258,280,326.
hope it really helped.
You could multiplied every thing by 3
Each time you got a product

Multiply
2y-2u9•3y9•u6
Simplify your answer as much as possible.

Answers

Step-by-step explanation:

this is you answer solved.

If a rectangle is dilated by a scale factor of 2 what is the new perimeter

Answers

Step-by-step explanation:

the new perimeter is 8 because add all sides

Multiply and simplify square root of 3ab * square root of 6ab^3

NEED HELP FAST!!!!!!

Answers

√3ab · √6ab³
√18a²b⁴
3ab²√2

Solve for x.
- 3x + 8y = 5
6x - 2y =10

Answers

Let us solve this system by substitution.

-3x + 8y = 5
6x - 2y = 10

According to equation 2,

6x - 2y = 10

6x = 10 + 2y

thus, x = 10 + 2y / 6

substituting the value of x in equation 1,

-3 ( 10 + 2y / 6) + 8y = 5

-30 - 6y + 8y = 5 x 6 = 30

-30 + 2y = 30

2y = 60

Thus, y = 30.

Substituting the value of y in equation 2,

6x - 2y = 10

6x - 2(30) = 10

6x - 60 = 10

6x = 70.

Thus, x = 70/6.

Thus, x = 70 / 6     ( and y = 30)

... the product of 86 and the depth of the river ...  into variable expression

Answers

A variable expression is an expression that contains variables or letters in their simplest form. If we assign real values to the variables, then we can evaluate the variable expression for that real value.

Since we do not know the depth of the river, we assign a variable to it.

We let the variable d, represent the depth of the river.

Then, the product of 86 and the depth of the river=86* d=86d

  product means multiplication either
86n
or
 
86*n which are the same thing